Underreporting of Lyme and Other Tick‐Borne Diseases in Residents of a High‐Incidence County, Minnesota, 2009. (8th July 2016) - Schiffman, E. K.; McLaughlin, C.; Ray, J. A. E.; Kemperman, M. M.; Hinckley, A. F.; Friedlander, H. G.; Neitzel, D. F.
Summary: Lyme disease (LD), anaplasmosis, babesiosis and other tick‐borne diseases (TBDs) attributed to Ixodes ticks are thought to be widely underreported in the United States. To identify TBD cases diagnosed in 2009, but not reported to the Minnesota Department of Health (MDH), diagnostic and procedural billing codes suggestive of tick‐borne diseases were used to select medical charts for retrospective review in medical facilities serving residents of a highly endemic county in Minnesota. Of 444 illness events, 352 (79%) were not reported. Of these, 102 (29%) met confirmed or probable surveillance case criteria, including 91 (26%) confirmed LD cases with physician‐diagnosed erythema migrans (EM). For each confirmed and probable LD, probable anaplasmosis and confirmed babesiosis case reported to MDH in 2009, 2.8, 1.3, 1.2 and 1.0 cases were likely diagnosed, respectively. These revised estimates provide a more accurate assessment and better understanding of the burden of these diseases in a highly endemic county.